2021
DOI: 10.1038/s41433-021-01439-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and visual difficulties in 36 low- and middle-income countries

Abstract: Background:Data on the association between visual difficulty and physical activity (PA) from low-and middle-income countries (LMICs) are scarce. Thus, the aim of the study was to investigate the association between visual difficulty and PA among adults from 36 LMICs, and to assess the mediators in this association. Methods:Cross-sectional, community-based, predominantly nationally representative data from the World Health Survey were analysed. The final sample included 199,110 individuals aged ≥18 years [mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our findings suggested that our conclusions regarding lighting and physical activity measures, while derived from a population enriched for persons with visual impairment, may also apply older adults without impairment, as our association did not differ by the level of VF damage, though sample size considerations may have made it harder to identify interactions. Literature showed that individuals with visual impairment have lower physical activity overall, 24 but they also spend more time at home and likely get most of their physical activity doing household tasks, such as cooking, sweeping, cleaning, etc. 9 Thus, improved lighting at home may play an especially important role in improving physical activity in older individuals with visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that our conclusions regarding lighting and physical activity measures, while derived from a population enriched for persons with visual impairment, may also apply older adults without impairment, as our association did not differ by the level of VF damage, though sample size considerations may have made it harder to identify interactions. Literature showed that individuals with visual impairment have lower physical activity overall, 24 but they also spend more time at home and likely get most of their physical activity doing household tasks, such as cooking, sweeping, cleaning, etc. 9 Thus, improved lighting at home may play an especially important role in improving physical activity in older individuals with visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Arthritis and chronic back pain are likely associated with sarcopenia owing to these conditions increasing levels of low-grade inflammation and reducing levels of physical activity [33,34]. In terms of vision and hearing problems, an increase in sarcopenia among these populations may again be owing to a low level of physical activity and high sitting time [35]. The association between multimorbidity and sarcopenia may be explained by the accumulative effect of single chronic conditions and their increased risk for sarcopenia.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%